40=6x+7(-x+17)

Simple and best practice solution for 40=6x+7(-x+17) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 40=6x+7(-x+17) equation:


Simplifying
40 = 6x + 7(-1x + 17)

Reorder the terms:
40 = 6x + 7(17 + -1x)
40 = 6x + (17 * 7 + -1x * 7)
40 = 6x + (119 + -7x)

Reorder the terms:
40 = 119 + 6x + -7x

Combine like terms: 6x + -7x = -1x
40 = 119 + -1x

Solving
40 = 119 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
40 + x = 119 + -1x + x

Combine like terms: -1x + x = 0
40 + x = 119 + 0
40 + x = 119

Add '-40' to each side of the equation.
40 + -40 + x = 119 + -40

Combine like terms: 40 + -40 = 0
0 + x = 119 + -40
x = 119 + -40

Combine like terms: 119 + -40 = 79
x = 79

Simplifying
x = 79

See similar equations:

| 15x+7=-8 | | -2x+4(x+1)=68 | | 3(q+7)=10q | | 13=4x-3(x-2) | | 37=-5x-2(4x+14) | | x^2+14x+20= | | -75=6x-7(2x+5) | | 14x+14=x | | -8X^2+58X-145=-5X^2+31X-85 | | cosx+sinx=0 | | 4(8-m)=2m+16 | | 1.99+1.99= | | 8i+(-4+5i)= | | -18=-2x-3(-2x-10) | | 2xy-8y+3x-12=0 | | R^2+16=10r | | 4x+6+x=5+9x+9 | | -7X^2+44X-50=-4X^2+29X-32 | | 3*x=568 | | 14=-2x-4(-4x+14) | | log[log(3x-5)]=0 | | 48=4x+5(x-3) | | x^2+y^2-16x+10y-3=0 | | x^2-4xy-5y^2=0 | | graphx^2-4xy-5y^2=0 | | x+x-19=87 | | 4h-(3h-10)=2h-(8-5h)+(3h-18) | | 2x^3+3x^2-32x+15=0 | | 9f+(-2f+6)=3f+(5-6f)-(-5f-18) | | 6w-(4w-7)=5w-(4-9w)+(-4w+35) | | 2x^2+6-24=x^2+1x | | 5X^2-47X+70=3X^2-31X+46 |

Equations solver categories